RHBDF1 deficiency suppresses melanoma glycolysis and enhances efficacy of immunotherapy by facilitating glucose-6-phosphate isomerase degradation via TRIM32 - Lei Wang; Yuan-Yuan Song; Yan Wang; Xiu-Xiu Liu; Yi-Lun Yin; Shan Gao; Fan Zhang; Lu-Yuan Li; Zhi-Song Zhang (Elsevier, 2023)
Melanoma is a dangerous form of skin cancer, making it important to investigate new mechanisms and approaches to enhance the effectiveness of treatment. Here, we establish a positive correlation between the human rhomboid family-1 (RHBDF1) protein and melanoma malignancy. We demonstrate that the melanoma RHBDF1 decrease dramatically inhibits tumor growth and the development of lung metastases, which may be related to the impaired glycolysis. We show that RHBDF1 function is essential to the maintenance of high levels of glycolytic enzymes, especially glucose-6-phosphate isomerase (GPI). Additionally, we discover that the E3 ubiquitin ligase tripartite motif-containing 32 (TRIM32) mediates the K27/K63-linked ubiquitination of GPI and the ensuing lysosomal degradation process. We prove that the multi-transmembrane domain of RHBDF1 is in competition with GPI, preventing the latter from interacting with NCL1-HT2A-LIN41 (NHL) domain of TRIM32. We also note that the mouse RHBDF1's R747 and Y799 are crucial for competitive binding and GPI protection. Artificially silencing the Rhbdf1 gene in a mouse melanoma model results in declined lactic acid levels, elevated cytotoxic lymphocyte infiltration, and improved tumor responsiveness to immunotherapy. These results provide credence to the hypothesis that RHBDF1 plays a significant role in melanoma regulation and suggest that blocking RHBDF1 may be an efficient technique for reestablishing the tumor immune microenvironment (TIME) in melanoma and halting its progression.